THE INFLUENCE OF WORK DISCIPLINE AND MOTIVATION ON EMPLOYEE PERFORMANCE AT PT. PELABUHAN CILEGON MANDIRI - Hadi Kurniawanto (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The study of Work Discipline and Motivation has a positive and significant effect on employee performance. The method in this research is quantitative descriptive method processed with multiple linear analysis which is used to test work discipline and motivation whether or not it affects employee performance. The number of samples in this study amounted to 52 people. At a significance level of 61.3%, it can be concluded that the independent variables (Performance Discipline and Motivation) used in the model affect the dependent variable (Employee Performance).